2019
DOI: 10.3390/ijerph16112006
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nursing Staff Attitudes toward Vaccinations through Academic Detailing: The HProImmune Questionnaire as a Tool for Medical Management

Abstract: Vaccinations remain the most effective way of preventing infection, disease, and mortality. Public health institutions consequently recommend vaccines to target groups, including healthcare workers, who are considered to be more at risk of exposure and transmission. The aim of this cross-sectional study is to assess, through the administration of a questionnaire, the nursing staff’s knowledge and attitude towards recommended vaccinations, and to explore the effects of a training course (carried out according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Vaccine hesitancy is a complex issue, especially amongst HCWs, and it requires ad hoc studies to understand the phenomenon in different contexts, in order to find ad hoc effective strategies to struggle it [24,26,40,41,56]. First of all, even and especially among healthcare personnel, it is necessary a have a cultural change about knowledge, attitudes and practices on vaccination through personalized training, such as academic detailing (educational outreach visit) and problem-based learning methodologies [43,44] or through the role of the occupational doctor who carries out annual health surveillance of workers [12]. As a matter of fact, this figure could play a key role by counseling HCWs with adequate information on the advantages and disadvantages of vaccination and non-vaccination, as defined by the Italian law [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccine hesitancy is a complex issue, especially amongst HCWs, and it requires ad hoc studies to understand the phenomenon in different contexts, in order to find ad hoc effective strategies to struggle it [24,26,40,41,56]. First of all, even and especially among healthcare personnel, it is necessary a have a cultural change about knowledge, attitudes and practices on vaccination through personalized training, such as academic detailing (educational outreach visit) and problem-based learning methodologies [43,44] or through the role of the occupational doctor who carries out annual health surveillance of workers [12]. As a matter of fact, this figure could play a key role by counseling HCWs with adequate information on the advantages and disadvantages of vaccination and non-vaccination, as defined by the Italian law [12].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about safety, necessity and effectiveness of influenza vaccination, the lack of awareness of being potentially responsible for the transmission to patients, the lack of time and absent or inadequate vaccination policies and services were identified as main reasons to delay or refuse flu vaccination, both in the literature and in our setting [24,25,[35][36][37][38]. Based on these evidences, starting from the 2015-2016 influenza season, different evidence-based strategies [24,[39][40][41][42][43][44][45] were progressively implemented in the following seasons (Table 1).…”
Section: Implemented Strategiesmentioning
confidence: 99%
“…A patient’s confidence on her or his nurse and/or doctor has been associated to their final acceptance or rejection of vaccines [ 5 , 6 ]. Despite the education programs of nurses and other professionals, a variability in their knowledge is still found amongst the nurses themselves, so that the design of refresher programs for these professionals could improve their vaccine coverage and their patient’s as well [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar evidence has been gathered in an Italian setting [ 13 , 14 , 15 , 16 ]. However, recent shreds of evidence relating to the Italian context have shown that specific organizational and educational interventions may have mixed results in ameliorating influenza VC [ 17 , 18 , 19 , 20 ]. Thus, research is important in finding variables useful in designing systematic interventions aimed at implementing HCWs vaccination coverage.…”
Section: Introductionmentioning
confidence: 99%